PENDAYAGUNAAN ZAKAT DI BIDANG PENDIDIKAN STUDI KASUS PADA LEMBAGA MANAJEMEN INFAQ (LMI) SUMSEL - Ilham Basrian Jasuma Putra; Muharudin; Edy Suryana (As-Sulthan Journal of Education, 2026)
One important aspect of a country's development is education. Education plays a very important role, even becoming the main foundation for the progress and welfare of society. However, in the effort to create equitable and quality education, there are still many obstacles, namely the cost of education. The government has prepared a budget of 20% of total state expenditure. However, this amount is still insufficient to meet existing needs. Therefore, an alternative innovation is needed to overcome this problem. One alternative that can be used is zakat funds. This study aims to determine the zakat utilization program in the field of education at LMI South Sumatra. This study uses a qualitative approach with a descriptive qualitative orientation. This approach was chosen because this study leads to a detailed and in-depth description of the actual conditions in the field. Based on the results of the study, it was found that LMI South Sumatra has several zakat utilization programs. First, the Inspirational Generation Scholarship, which is intended to provide educational assistance to final year students. Second, assistance for Quran teachers, which is provided to Quran teachers in the form of financial assistance to help meet their basic needs and support the continuity of their Quran teaching activities.